Constituting Chileans: the Cabildos of October 2019 and the trouble of instrumental participation. (3rd September 2021) - Ureta, Sebastián; Cortes, Alexis; Martínez, Jordan; Tello, Pedro; Vera, Fernanda; Valenzuela, Cristian
ABSTRACT: Besides large-scale rallies on the streets, the Chilean estallido social that commenced in October 2019, was noteworthy by the sudden emergence throughout the country of local-based and largely improvised instances of direct citizen participation, known as cabildos . Adopting multiple formats, cabildos invited people to meet and discuss a wide variety of public issues. Emerging at a moment in which national authorities agreed to hold a referendum to replace the country's constitution, cabildos were considered a blueprint for the mechanism needed to integrate vast sectors of the population to deliberate on constitutional matters. This article explores such hypotheses, using analytic tools from science and technology studies, and based on a sample of cabildos held between October and November 2019. By focusing on issues such as materials involved in cabildos, the experience they formatted and the publics that emerged through them, we aim to show that cabildos could not be seen merely as a novel instrument for citizen deliberation. On the contrary, we sustain they represented a particular kind of citizen-led democratic experience; one on which the multiple paradoxes characterising post-authoritarian Chilean society are fairly evident. To properly become a basis for further democratisation, it is concluded, cabildos should be reflexively intervened, looking to strengthen its deliberative potential while controlling its antipolitical bias.